2023
DOI: 10.3389/fpls.2023.1236838
|View full text |Cite
|
Sign up to set email alerts
|

Cotyledon peeling method for passion fruit protoplasts: a versatile cell system for transient gene expression in passion fruit (Passiflora edulis)

Abstract: Passion fruit (Passiflora edulis) is a perennial evergreen vine that grows mainly in tropical and subtropical regions due to its nutritional, medicinal and ornamental values. However, the molecular biology study of passion fruit is extremely hindered by the lack of an easy and efficient method for transformation. The protoplast transformation system plays a vital role in plant regeneration, gene function analysis and genome editing. Here, we present a new method (‘Cotyledon Peeling Method’) for simple and effi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 41 publications
(74 reference statements)
0
1
0
Order By: Relevance
“…During the process of sugarcane protoplast preparation, Wu et al [ 51 ] showed a trend of first increasing and then decreasing protoplast yield and viability with increasing enzymolysis time. Adjei et al [ 52 ] found that the optimal enzymolysis time for mango protoplasts was 12 h, while Wang et al [ 53 ] used 2 h for separation of passion fruit protoplasts. In this experiment, the enzymatic hydrolysis of plant tissue was observed every half hour to ensure that the protoplasts were not damaged or insufficiently digested due to enzymolysis time.…”
Section: Discussionmentioning
confidence: 99%
“…During the process of sugarcane protoplast preparation, Wu et al [ 51 ] showed a trend of first increasing and then decreasing protoplast yield and viability with increasing enzymolysis time. Adjei et al [ 52 ] found that the optimal enzymolysis time for mango protoplasts was 12 h, while Wang et al [ 53 ] used 2 h for separation of passion fruit protoplasts. In this experiment, the enzymatic hydrolysis of plant tissue was observed every half hour to ensure that the protoplasts were not damaged or insufficiently digested due to enzymolysis time.…”
Section: Discussionmentioning
confidence: 99%